2022
DOI: 10.3390/su142013388
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Systematic Strategic Planning and Strategic Business Innovation on the Sustainable Performance of Manufacturing SMEs: The Case of Palestine

Abstract: Small and Medium Enterprises’ (SMEs) impact on economic growth is widely acknowledged. Nevertheless, the literature lacks empirical evidence as to how the sustainable performance of manufacturing SMEs in developing countries with unstable and turbulent business environments, such as Palestine, could be enhanced. Relying on the Triple Bottom Line (TBL), Resource-based View (RBV) theory, and sustainable performance literature, this study explores the influence of systematic strategic planning (SSP) and strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…They found that strategic agility significantly affects organizational performance and innovation capability, and innovation capability improves the relationship between strategic agility and organizational performance. Dwikat et al [33] found that strategic business innovation and systematic strategic planning enhance the sustainability of Palestinian small and medium manufacturing enterprises.…”
Section: Background Research and Hypothesismentioning
confidence: 99%
“…They found that strategic agility significantly affects organizational performance and innovation capability, and innovation capability improves the relationship between strategic agility and organizational performance. Dwikat et al [33] found that strategic business innovation and systematic strategic planning enhance the sustainability of Palestinian small and medium manufacturing enterprises.…”
Section: Background Research and Hypothesismentioning
confidence: 99%
“…Family-owned businesses constitute more than 70% of total enterprises that operate within the Palestinian territories (Dwikat et al, 2022;Sultan, 2014;Sultan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These challenges can be categorized into three main issues: intrinsic, structural, and internal. The first challenge is external because of the political conflict that restricts economic growth in some developing countries [11]. Likewise, the second challenge is internal and is classified as a structural obstacle attributed to the weak role of the policy of some companies and sustainable development institutions in controlling, organizing and strengthening the environment conducive to the prosperity of the private sector and the manufacturing industry [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The third major challenge, which will be the main focus of this study, is the internal issues at the level of the organization, which are attributed to the application of best management practices at the level of the company, such as the implementation of sound strategic planning and the application of sustainable development standards. Moreover, the majority of small and medium-sized companies are family businesses that have started to face real challenges to their survival and sustainability, which has led to the bankruptcy of a large number of small and medium-sized companies [15][16][17][18][19][20]. More precisely, previous studies of the strategic planning sector revealed that these challenges can be summed up by the fact that the market share of locally manufactured products in the local market does not exceed 20 percent [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation